2013
DOI: 10.1038/jp.2013.79
|View full text |Cite
|
Sign up to set email alerts
|

Brain wave maturation and neurodevelopmental outcome in extremely low gestational age neonates

Abstract: Among extremely preterm infants, the rate of maturational changes in brain wave characteristics between 28 and 36 weeks' postmenstrual age is not predictive of developmental abilities at 18 to 22 months adjusted age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…To establish easy algorithms for aEEG interpretation, several authors have reported maturational changes of electrocortical activity according to both postnatal and gestational age. Recent studies have pointed out a correlation of early aEEG parameters with short- and long-term neurological outcome [3, 14, 18, 25, 27, 29]. In this study, we refer to and compare the classifications by Hellström-Westas et al [11] and the aEEG maturation score introduced by Burdjalov et al in a single center cohort of prematurely born infants ≤32 weeks gestation [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To establish easy algorithms for aEEG interpretation, several authors have reported maturational changes of electrocortical activity according to both postnatal and gestational age. Recent studies have pointed out a correlation of early aEEG parameters with short- and long-term neurological outcome [3, 14, 18, 25, 27, 29]. In this study, we refer to and compare the classifications by Hellström-Westas et al [11] and the aEEG maturation score introduced by Burdjalov et al in a single center cohort of prematurely born infants ≤32 weeks gestation [6].…”
Section: Discussionmentioning
confidence: 99%
“…Burdjalov total scores from aEEGs obtained within the first 6 weeks of life in infants ≤30 gestational weeks were associated with perinatal factors that are known to predict adverse neurodevelopmental outcome [18]. On the other hand, the rate of brain wave maturation between 28 and 36 weeks gestational age in preterm infants <28 weeks does not predict neurological development at 18 to 22 months corrected age [27]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that the amplitude integrated EEG (aEEG) can predict long-term outcome, with specificity ranging from 73 to 89% and sensitivity ranging from 56 to 87% (15)(16)(17). To date, however, no standardized method for the accurate prediction of long-term outcome in very preterm infants has been successfully translated into clinical practice.…”
mentioning
confidence: 99%
“…[48] сообщают, что данные, полученные при регистрации электрической активности головного мозга, коррелируют с результатами рутинной ЭЭГ. В свою очередь, ряд исследователей [49,50] подтверждают диагностическую и прогностическую ценность этого метода как для доношенных, так и для недоношенных детей. K. Klebermass и коллеги указывают, что специфичность а-ЭЭГ, проведенной в течение первых двух недель жизни у ребенка, в отношении которого не применяется медикаментозная седация, обезболивающая и противосудорожная терапия, составляет 98%.…”
Section: нейрофизиологические методы в исследовании недоношенных детеunclassified